2015
DOI: 10.1039/c5cc06595j
|View full text |Cite
|
Sign up to set email alerts
|

Separation of cobalt and nickel using a thermomorphic ionic-liquid-based aqueous biphasic system

Abstract: A [P44414][Cl]-NaCl-H2O ionic liquid-based aqueous biphasic system shows promising results for the separation of cobalt(II) and nickel(II) by homogeneous liquid-liquid extraction. The extracting phase consists of a hydrophilic ionic liquid that is salted-out by sodium chloride, indicating that there is no need for using hydrophobic ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…These systems are based on hydrophilic ILs that, once mixed with a specific inorganic salt in water, yield the formation of two immiscible aqueous phases—a salt‐rich and an IL‐rich phase, respectively. Few IL‐ABS were previously applied to metal ion extraction due to their limited stability at the low pH required to prevent metal hydrolysis . In addition, in any metal extraction process, acids are used to leach the metal from ores or waste devices.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These systems are based on hydrophilic ILs that, once mixed with a specific inorganic salt in water, yield the formation of two immiscible aqueous phases—a salt‐rich and an IL‐rich phase, respectively. Few IL‐ABS were previously applied to metal ion extraction due to their limited stability at the low pH required to prevent metal hydrolysis . In addition, in any metal extraction process, acids are used to leach the metal from ores or waste devices.…”
Section: Figurementioning
confidence: 99%
“…Onghena et al . reported the formation of ABS using [P 44414 ][Cl] and NaCl and their application to the separation of cobalt from nickel.…”
Section: Figurementioning
confidence: 99%
“…[10,11] Another type of extracting systems,s o-called ionic-liquid-based aqueous biphasic systems (IL-ABS) have been used in the last decade for extracting neutral compounds from an aqueous phase. [16] In addition, in any metal extraction process,a cids are used to leach the metal from ores or waste devices. [16] In addition, in any metal extraction process,a cids are used to leach the metal from ores or waste devices.…”
mentioning
confidence: 99%
“…Onghena et al [16] reported the formation of ABS using [P 44414 ][Cl] and NaCl and their application to the separation of cobalt from nickel. Ac omparison of the phase diagrams for these systems (compare Figure S2) [20] while the proposed AcABS allows for the direct "one-pot" extraction of metals from leachates.…”
mentioning
confidence: 99%
See 1 more Smart Citation